Evolution of magnetic and magnetoresistive properties of sputtered NiFe/Cu/Co/Cu nanostructures under ageing and annealing - Roschenko, S.T.; Shipkova, I.G.; Chekrygina, Yu.I. (Functional Materials, 2009)
Magnetic and magnetoresistive properties of sputtered Ni₈₀Fe₂₀(4-6 nm)/Cu(2-10 nm)/Co(2 nm)/Cu(2 nm) nanostructures have been studied after room temperature ageing and thermal annealing at 75-150°C. Magnetic properties of Co/Cu bilayer and NlFe/Cu one were investigated. The transformations of field dependences of magnetoresistance, and the nanostructure hysteresis loops have been considered. The evolution of characteristics in the nanostructure as a whole is supposed to be due to changes in magnetic properties of the upper Co/Cu layer, namely, to the magnetic anisotropy deterioration and the appearance of separate single-domain and superparamagnetic particles. Досліджено магнітні та магніторезистивні властивості наноструктур Ni₈₀Fe₂₀(4- 6 nm)/Cu(2-10 nm)/Co(2 nm)/Cu(2 nm), виготовлених методом іонно-плазмового розпорошення, після витримки у часі при кімнатній температурі та відпалу в інтервалі температур 75-150°С. Досліджено магнітні властивості бішарів Co/Cu та NiFe/Cu. Проведено аналіз трансформацій польових залежностей магнітоопору та петель гістерезису наноструктур. Запропоновано пояснення еволюції характеристик всієї наноструктури як результат зміни магнітних властивостей верхнього шару Co/Cu, а саме, руйнування в ньому магнітної анізотропії, а також появою ізольованих однодоменних та суперпарамагнітних частинок. Исследованы магнитные и магниторезистивные свойства наноструктур Ni₈₀Fe₂₀(4- 6nm)/Cu(2-10 nm)/Co(2 nm)/Cu(2 nm), изготовленных методом ионно-плазменного распыления, после временной выдержки при комнатной температуре и отжига в интервале температур 75-150°С. Исследованы магнитные свойства бислоев Co/Cu и NiFe/Cu. Проведен анализ трансформаций полевых зависимостей магнитосопротивления и петель гистерезиса наноструктур. Предложено объяснение эволюции характеристик наноструктуры как результат изменения магнитных свойств верхнего слоя Co/Cu, а именно, разрушения в нем магнитной анизотропии, а также появлением изолированных однодоменных и суперпарамагнитных частиц.